Dental Implant Treatment and Immediate Functional Loading (1). Case Report and Considerations: Extended Treatment Options Using the Strategic Implant® and Indications and Objectives for Comprehensive Dental Implant Treatment - Ihde, Stefan (Ann Maxillofac Surg, 2019)
While materials for the restoration of teeth and new (digital) technologies develop fast, the choices of the treatment provider and the patients get wider. Choosing an adequate and long-lasting treatment is a question of “doing the right thing,” and only after that, the dentist has to think about the question how to do the work properly. This case report explains and illustrates a case, where an adequate treatment by means of conventional dentistry would not have been possible on one hand, and where treatment with the technology of the Strategic Implant(®) provided a perfect result within only a few days. Thanks to this technology, patients can be treated with fixed prostheses regardless of the amount of residual bone. Recently, published long-term observations on large amounts of implants have shown that the results are sustainable.